2021
DOI: 10.3390/app11073130
|View full text |Cite
|
Sign up to set email alerts
|

Towards Predicting Student’s Dropout in University Courses Using Different Machine Learning Techniques

Abstract: Early and precisely predicting the students’ dropout based on available educational data belongs to the widespread research topic of the learning analytics research field. Despite the amount of already realized research, the progress is not significant and persists on all educational data levels. Even though various features have already been researched, there is still an open question, which features can be considered appropriate for different machine learning classifiers applied to the typical scarce set of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 35 publications
1
37
1
1
Order By: Relevance
“…Through the intensive statistical analyses carried out by the researchers in this study, it was found that the CEAWR after the preparatory year is more convincing in assessing the performance of students, and therefore enrollment in colleges is more suitable for this performance. These findings align with other research findings that prove the usefulness of the first year on the prediction of students' success (Bruinsma and Jansen 2007;Van Der Zanden et al 2019;Beaulac and Rosenthal 2019;Culver and Bowman 2020;Kabathova and Drlik 2021).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Through the intensive statistical analyses carried out by the researchers in this study, it was found that the CEAWR after the preparatory year is more convincing in assessing the performance of students, and therefore enrollment in colleges is more suitable for this performance. These findings align with other research findings that prove the usefulness of the first year on the prediction of students' success (Bruinsma and Jansen 2007;Van Der Zanden et al 2019;Beaulac and Rosenthal 2019;Culver and Bowman 2020;Kabathova and Drlik 2021).…”
Section: Discussionsupporting
confidence: 91%
“…The study also found that some factors, such as race, sex, and ACT score, may affect first-year seminars. In a recent study, Kabathova and Drlik (2021) discussed the use of learning analytics to explore the levels of student dropout from university studies using the available educational data. The study attempted to address appropriate features for machine learning classifiers used e-learning courses, which provide access to tests, assignments, exams, and projects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is often presumed by education policy and institutions that less persistent students are probably not sufficiently prepared. The review of the literature shows that many studies find a correlation between lower entry scores and failures in the first academic year, whereby a low level of persistence is developed due to poor academic performance (Kabathova and Drlik 2021;Reason 2009). In contrast, the first successful entry, favorable exam results, and good grades in the initial years all increase persistence.…”
Section: Students' Persistencementioning
confidence: 99%
“…Most adopted algorithms are Logistic Regression, Decision Tree, Naive Bayes Classifier, Support Vector Machine, Random Forest, Neural Network. Results proved that Random Forest classifier obtained best accuracy with 93%, precision reached 86%, F1 score was 91% compared to other classifiers [26]. Researchers have collected real students' data with various information namely personal, economic, and academic records and evaluated by statistics values to find most effective one.…”
Section: Literature Reviewmentioning
confidence: 99%